Dinamika Kebijakan Dividen Pasca-Pandemi: Studi Empiris pada Perusahaan Manufaktur di Indonesia - Dessy Arisanti; Burhanudin Burhanudin (Owner : Riset dan Jurnal Akuntansi, 2026)
This study examines the dynamics of dividend policy in manufacturing companies listed on the Indonesia Stock Exchange during the post-pandemic period of 2020–2024. Using panel data regression analysis, 40 manufacturing firms were selected through purposive sampling and analyzed using Eviews 12 software. Empirical evidence on corporate dividend policy behaviour in the post-pandemic period, particularly in developing countries, is still limited and shows inconsistent results. The results show that leverage and profitability have a negative and significant effect on dividend policy. This finding contradicts the signalling theory perspective and is important because it indicates that in the post-pandemic period, manufacturing companies in Indonesia prioritise profit retention to strengthen financial resilience and support reinvestment rather than using dividends as a performance signal. Furthermore, the negative and significant influence of leverage indicates that the higher a company's dependence on debt-based financing, the more limited its ability to distribute dividends to shareholders. Meanwhile, collateral assets, free cash flow, and investment opportunity set did not show a significant influence. The main contribution of this study lies in confirming that the relationship between profitability and dividend policy is contextual and not universal, especially in post-crisis emerging markets. In practical terms, the results of this study have implications for investor and company managers in evaluating the sustainability of dividends in uncertain economic conditions.